Meningeal Hemangiopericytoma in 33-Year-Old Female; a Case Report - Abdollahi, Alireza (Iran J Pathol, 2016)
Intracranial hemangiopericytomas (HPC) are rare vascular tumors. They account for 0.4% of primary central nervous system tumors. HPC is more commonly located supratentorially and tends to occur in a younger age group, with average age at presentation of 38–42 years. The tumor was found throughout the entire CNS, usually superficially and closely related to the meninges. Moreover, they have a strong tendency for local recurrence and extracranial metastasis. Given the clinical, pathological and imaging similarities between Hemangiopericytoma and angioblastic/anaplastic meningioma and the necessity of differentiating these two (choosing the proper treatment and prognosis), we present a report of meningeal Hemangiopericytoma tumor in a 33-year-old female. Our study suggests that in addition to routine histopathological examination, immunohistochemical study is essential to differentiate it from other differential diagnosis.